2014
DOI: 10.1063/1.4898809
|View full text |Cite
|
Sign up to set email alerts
|

Mineralization and optical characterization of copper oxide nanoparticles using a high aspect ratio bio-template

Abstract: Organized chains of copper oxide nanoparticles were synthesized, without palladium (Pd) activation, using the M13 filamentous virus as a biological template. The interaction of Cu precursor ions with the negatively charged viral coat proteins were studied with Fourier transform infrared spectroscopy, transmission electron microscopy, and energy dispersive x-ray spectroscopy. Discrete nanoparticles with an average diameter of 4.5 nm and narrow size distribution were closely spaced along the length of the high a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…Zaman et al have reported on bio-templated mineralization of M13 phages displaying three Glu units on their major coat proteins. [26] In that study, M13 viruses were first incubated with Cu(II) solution resulting in phage bundle formation that was similarly observed in our study for wild-type fd phages (Figure 4). Formation of phage agglomerates have been previously demonstrated by various studies elsewhere due to the electrostatic interactions between negatively charged virus molecules and positively charged counterions.…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…Zaman et al have reported on bio-templated mineralization of M13 phages displaying three Glu units on their major coat proteins. [26] In that study, M13 viruses were first incubated with Cu(II) solution resulting in phage bundle formation that was similarly observed in our study for wild-type fd phages (Figure 4). Formation of phage agglomerates have been previously demonstrated by various studies elsewhere due to the electrostatic interactions between negatively charged virus molecules and positively charged counterions.…”
Section: Resultssupporting
confidence: 75%
“…Phage bundle formation has been previously published by various research groups elsewhere demonstrating the supramolecular virus assembly formation due to the electrostatic interactions between negatively charged phage filaments and positively charged counterions. [26][27][28] On the contrary, engineered H and HGFANVA phages were observed to form more elongated fibrous structures coated with some form of mineralized Cu particles implied by the white colored filaments (Figure 4, 10 12 vir mL −1 ). Interestingly, before Cu(II) exposure, H and HG-FANVA phages were observed as darker networking filaments similar to wild-type fd viruses (Figure 3).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The ultravioletvisible (UV-vis) absorption results of an aqueous solution of methylene blue checked in the presence of ZnO NPs at different time intervals. The absorption peak decreased gradually with the extension of the exposure times, indicating the photocatalytic degradation [36][37][38][39].…”
Section: Photocatalytic Activitymentioning
confidence: 97%
“…The ultravioletvisible (UV-vis) absorption results of an aqueous solution of methylene blue checked in the presence of ZnO NPs at different time intervals. The absorption peak decreased gradually with the extension of the exposure times, indicating the photocatalytic degradation [36][37][38][39].…”
Section: Photocatalytic Activitymentioning
confidence: 99%